Influence of Oxygen Concentration on Plasma Dynamic Synthesis Product in Fe-O System; Solid State Phenomena; Vol. 265 : Materials Engineering and Technologies for Production and Processing III - Shanenkov I. I. Ivan Igorevich (2017, 2017)
Title screen